The Single Predictor Of The Influence Of Headmasters Leadership On Special Education Teachers Job Satisfaction In Malaysia - et. al., Shahrulliza binti Saharudin, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Special education leadership is an aspect of comprehensive management related to special education operations that includes knowledge, leadership style and also the welfare of teachers and students. Good leadership for a special education program should implement the process of planning, organizing, directing and controlling the members of the organization as well as using all organizational resources to achieve specific goals for special education. The leadership practiced in special education needs to make the special education program improve and be able to carry out its functions properly. This quantitative study was conducted to examine the single predictor of headmasters leadership and teacher workload on job satisfaction of teachers of special education integration program (PPKI) in the state of Johor Malaysia. A total of 400 respondents were involved in answering the questionnaire and the findings were analyzed using structural equation modeling (SEM) approach with AMOS 21 software. The results found that these two single predictors recorded high effect size values ​​on teacher job satisfaction. This proves that headmaster leadership and teacher workload play a significant role on the job satisfaction of special education teachers. The findings of this study are expected to provide a clear picture of this issue.